Abattoirs, Meat Processing and Managerial Challenges: A Survey for Lagging Rural Regions and Food Entrepreneurs in Ontario, Canada. (April 2014) - Charlebois, Sylvain; Summan, Amit
The meat processing sector is a significant contributor to the food economy, particularly in the Canadian province of Ontario. The sector contributed over $8 billion to the food manufacturing sector, and it employed over 647, 000 people in 2011. In Ontario, there has been a great decline in the number of provincially licensed plants in the past 7 years. There were 183 provincially licensed slaughter plants in 2005; this number decreased to 142 by 2012. This study seeks to understand what challenges abattoirs and processors are currently facing and why abattoirs have closed in the past. The research shows that the major challenges facing abattoirs and processors are: regulatory challenges and administrative-related responsibilities, high overhead costs and a limited skilled labour force. These challenges have been mitigated by consumer preferences toward local food. Limitations of the study are presented and foundations for further research are suggested.